Conservative Management of a Scar Abscess formed in a Cesarean-induced Isthmocele - Boukrid, Meriem; Dubuisson, Jean (Frontiers in Surgery, 2016)
Background: Abscesses located in the caesarean-section induced isthmoceles are rarely encountered and are usually treated surgically, mostly by hysterectomy. Case description: We here report the case of a 40-year-old primiparous woman presenting a symptomatic abscess in the isthmocele 10 years after a caesarean section. She was treated by antibiotics and was closely monitored by clinical evaluation, ultrasonography and pelvic magnetic resonance imaging. This treatment led to complete resolution of symptoms and a disappearance of the abscess at imagery. Conclusion: Our report shows that a conservative medical management of isthmocele abscesses can be an effective approach in women wishing to preserve their uterus.